Synthesis and Characterizations of Fe-Doped NiO Nanoparticles and Their Potential Photocatalytic Dye Degradation Activities - Minisha, S.; Johnson, J.; Mohammad Wabaidur, Saikh; Gupta, Jeetendra Kumar; Aftab, Sikandar; Siddiqui, Masoom Raza; Lai, Wen-Cheng (Sustainability, 2023)
Recently, the preparation of smart multifunctional hybrid nanoparticles has captured significant interest in versatile areas, including medicine, environment, and food, due to their enhanced physicochemical properties. The present study focuses on the synthesis of Fe-doped NiO nanoparticles by the coprecipitation method using the sources of nickel (II) acetate tetrahydrate and iron (III) nitrate nonahydrate. The prepared Fe-doped NiO nanoparticles are characterized by X-ray diffraction, Fourier transform infrared spectroscopy, UV–visible spectroscopy, field-emission scanning electron microscopy, transmission electron microscopy, and X-ray photon spectroscopic analysis. The XRD results clearly confirm the face-centered cubic structure and polycrystalline nature of the synthesized Fe-NiO nanoparticles. The Tauc plot analysis revealed that the bandgap energy of the Fe-doped NiO nanoparticles decreased with the increasing concentration of the Fe dopant from 2% to 8%. The XPS analysis of the samples exhibited the existence of elements, including Fe, Ni, and O, with the absence of any surplus compounds. The FE-SEM and TEM analyses proved the formation of nanostructured Fe-NiO with few spherical and mostly unevenly shaped particles. Further, the photocatalytic efficiency of the prepared Fe-doped NiO nanoparticles were identified by using the cationic dye rhodamine B (Rh-B). The photocatalytic results proved the 8% of Fe doped with NiO nanoparticles achieved 99% of Rh-B degradation within 40 min of visible-light irradiation. Hence, the results of the present study exemplified the Fe-doped NiO nanoparticles have acted as a noticeable photocatalyst to degrade the Rh-B dye.